An algorithm for the assessment of several small rates - Sakalauskas, Leonidas; Vaičiulytė, Ingrida (Lietuvos matematikos rinkinys, 2012)
The present paper describes the empirical Bayesian approach applied in the estimation of several small rates. Modeling by empirical Bayesian approach the probabilities of several rare events, it is assumed that the frequencies of events follow to Poisson’s law with different parameters, which are correlated Gaussian random values. The unknown parameters are estimated by the maximum likelihood method computing the integrals appeared here by Hermite–Gauss quadratures. The equations derived that are satisfied by maximum likelihood estimates of model parameters.
Keywords: Bayesian approach; likelihood method; Poisson–Gaussian model